The Role Of Using The Technology Of Education Of Patriotic Qualities In Students Of A Professional Educational Institution (Czech Journal of Multidisciplinary Innovations, 2022)
Educating our growing children, who are considered the future of our country, in the spirit of patriotism in the conditions of information diversity is one of the most sacred, noble, precious and honorable tasks for every pedagogue, educator, parent and coach. This issue is one of the priority directions of our state policy.